Pengaruh Motivasi Terhadap Kinerja Karyawan PT. Duren Mandiri Fortuna, TBK Bagian Rotary Dan Asah Pisau Desa Sungai Duren Kec. Jaluko Kab.Muara Jambi - Olyvia Dewi Fortuna (Science of Management and Students Research Journal (SMS), 2019)
This study aims to measure the influence of employee motivation and performance at PT Mandiri Mandiri Fortuna. This study is useful to examine whether motivation influences employee performance which aims to describe employee motivation and performance and to know and analyze the influence of motivation and performance of PT Duren employees Mandiri Fortuna. This study uses qualitative and quantitative methods with analytical methods using simple linear regression, normality test, t test. and also assisted with softwear spss ver 20. The results of simple linear regression analysis Y = 18.603 + 0.445 X. In the partial test it was obtained t table (2.00575 <5.915). This means that t count is greater than t table so H0 is rejected and Ha is accepted, meaning that there is an influence between motivation on employee performance.